Speed Tracking and Synchronization of a Dual-Motor System via Second Order Sliding Mode Control. (4th September 2013) - Chen, Wei; Wu, Yifei; Du, Renhui; Chen, Qingwei; Wu, Xiaobei
Abstract : Dual-motor systems have been widely used in industrial applications, and speed synchronization of the motors can always be deteriorated by system parameter uncertainties and load torque perturbations. In this paper, a new robust control strategy for the dual-motor systems is developed by incorporating second order sliding mode control (2-SMC) techniques. The strategy is to design chatting-free control laws to stabilize speed tracking of each motor while synchronizing their velocity. In the proposed scheme, firstly, speed controller for a single motor is designed to eliminate the effects of system parameter variations and load torque perturbations. Secondly, a cross-coupled architecture based synchronous controller is designed to reduce speed error of the motors caused by characteristic inconsistency and unbalanced load torque. Stability of the closed loop system is analyzed by Lyapunov theory; it is proven that both speed tracking errors and synchronous error can converge to zero. Finally, experiments are performed to examine the effectiveness of the developed controllers. Experimental results will show the good performance of the proposed control scheme.